The Quality of Public Services in the South Margahayu Village, Bandung Regency - Salmania, Dinda; Deden Suhendar (GoResearch - Research & Publishing House, 2024)
This study aims to understand how the quality of public services in the field of population administration in South Margahayu Village, Margahayu District, Bandung Regency. This research was motivated by various obstacles that are still faced in an effort to improve the quality of public services in the village. The methods used in this research include interviews, documentation, and direct observation. The data obtained was analyzed through a process of reduction, presentation, and conclusion drawing. To ensure the accuracy of the data, the source triangulation method was used by verifying information from different parties and at different times. The selection of informants was based on certain criteria, involving service providers and people who use the service. The results showed that public services at the South Margahayu Village Office have not fully met the five dimensions of service quality. Some aspects that need to be improved include providing better facilities, increasing employee discipline and reliability, and improving employee attitudes in handling community complaints.